Personalized care in neuro-oncology coming of age: why we need MGMT and 1p/19q testing for malignant glioma patients in clinical practice - Weller, Michael; Stupp, Roger; Wick, Wolfgang (Neuro-Oncology, 2012)
Abstract. Histological subtyping and grading by malignancy are the cornerstones of the World Health Organization (WHO) classification of tumors of the central
Gesehen am 16.05.2019